Identificação e avaliação morfofuncional das espermatogônias-tronco do homem - André Lucas Caldeira Brant de Oliveira (2021)
Sperm production in humans is dependent on a population of diploid spermatogonial stem cells (SSCs) that are the foundation of the spermatogenic process. Therefore, studying SSC behavior is extremely relevant, since any alteration in its biology may cause fertility impairments. Currently, human spermatogonia are morphofunctionally divided into: undifferentiated Adark (with and without nuclear vacuole, AdVac and AdNoVac, respectively) and Apale; and differentiating type B spermatogonia. Despite that, there is a lack of information regarding the association of spermatogonial phenotype and gene expression, mitotic activity, and developmental dynamics. This issue is due to not only the biological heterogeneity of spermatogonia, but also the difficulty in obtaining, human testicular samples, which hinders the development of studies that could recognize their morphology and behavior, especially in terms of SSCs. By obtaining testis samples from seven fertile human donors, the present study aimed to investigate the undifferentiated spermatogonial behavior, in vivo, concerning the association of its phenotype with kinetic, cell proliferation and apoptosis, niche, expression of spermatogonial markers as well as colonizing activity. To this end, histomorphometric and immunostaining assays were initially performed to evaluate the expression of spermatogonial markers. Subsequently, functional analyses were carried out through xenotransplantation of sorted spermatogonial stem cell suspensions to infertile immunodeficient mice. Herein it was demonstrated for the first time in humans that (a) AdVac spermatogonia corresponds to the smallest population (10%) of the testis, (b) which are relatively quiescent cells (10% in mitotic activity), (c) and being positioned nearby blood vessels while in G0 state. In addition, (d) AdVac express spermatogonial markers in a primitive undifferentiated way: 100% UTF1+, with the quiescent ones expressing it in a high manner; 95% TSPAN33+; 88% GFRA1+; and without expressing c-KIT. Regarding SSC behavior, it was shown that undifferentiated spermatogonia with low mitotic activity, such as the TSPAN33+, (20% MCM7+, and covering 94% of AdVac) have low potential to colonize and proliferating after xenotransplantation to infertile mice. Taken together, the present study presents AdVac as the reserve undifferentiated spermatogonia of the human testis and that primitive undifferentiated spermatogonia are ineffective to colonize a permissive testicular environment after xenotransplantation. Thus, herein it was clarified aspects related to the human undifferentiated spermatogonial biology, which will be extremely important for future studies, especially those related to clinical investigations such as spermatogonial stem cell-based therapies.